2011
DOI: 10.1039/c1jm11592h
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of phytochemical-stabilized Au nanoparticles under ambient conditions and their biocompatibility and antioxidative activity

Abstract: Green chemical synthesis of Au nanoparticles (NPs) has been of great interest because of its potential biomedical applications. In this study, we successfully produced phytochemical-induced Au NPs cofunctionalized with gallic acid, protocatechuic acid, and isoflavone. They have a strong antioxidant effect and serve as effective reducing agents, inducing the immediate passivation of Au NPs. The properties of these green chemical Au NPs were characterized by TEM, UV/Vis and FT-IR spectroscopy, and z-potential me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 36 publications
3
54
0
Order By: Relevance
“…5b. This may be achieved by means of high repulsive and attractive forces exist between each nanoparticle (Lee et al 2011). The observed result is well correlated with the TEM studies (Fig.…”
Section: Dynamic Light Scattering Studiessupporting
confidence: 78%
“…5b. This may be achieved by means of high repulsive and attractive forces exist between each nanoparticle (Lee et al 2011). The observed result is well correlated with the TEM studies (Fig.…”
Section: Dynamic Light Scattering Studiessupporting
confidence: 78%
“…The zeta potential value of Ag Nanoparticles, -31.4 mV, indicated the high stability of AgNanoparticles (Figure 9), it may be due to the high repulsive and attractive force exist between Nanoparticles [24] The similar study had been reported for biosynthesized Silver Nanoparticles by Gracilaria corticata, zeta potential was -26.2 mV [25].…”
Section: Dynamic Light Scattering (Dls)supporting
confidence: 49%
“…The nanoparticles might penetrate into the cell via endocytotic mechanisms such as phagocytosis, pinocytosis, nonspecific endocytosis, receptor-mediated endocytosis, etc. 47,48 TEM studies were also performed to track a detailed cellular uptake of SPIONs ( Figure 5B). The internalization of SPIONs is highly related to their coating material, shape, and size.…”
mentioning
confidence: 99%